Pengaruh Aerasi dan Suhu Nutrisi terhadap Sawi Samhong (Brassica juncea L.) dengan Hidroponik Rakit Apung - Sapto Wibowo (Paspalum: Jurnal Ilmiah Pertanian, 2023)
The floating raft is a simple hydroponic system, in which the nutrient solution stagnates without circulation, causing the condition of the dissolved oxygen content in the nutrient solution to be less than optimal for plant growth. To improve aeration can be done using an aerator and the addition of blocks of ice in the nutrient solution. This study aims to determine the effect of aeration using an aerator and temperature regulation of the nutrient solution on mustard samhong using floating raft hydroponics. There are two independent variables used, namely aeration (A) which is grouped into without aerator (A0) and with aerator (A1), and nutrient temperature (T) which is grouped into T1 (18o-20oC), T2 (22o-24oC), and T3 (26o-28oC). Data on plant height, number of leaves, and plant weight were analyzed using a two-way ANOVA test at the 5% level. The results showed that the aerator increased the dissolved oxygen content in the nutrient solution so that it had a better effect on plants, and the nutritional temperature that has the best effect is T1.